Numerical simulation of the effect of atmospheric condition on the lightning strike for wind turbine - Yang, Ning; Jiang, Wei; Jin, Chenlu; Zhang, Shuqin; Hou, Wenhao (Frontiers in Earth Science, 2023)
The risk of lightning exposure increases as wind turbine size increases, and lightning accidents have grown up to be a severe threat to wind turbines. The present paper focuses on the influence of the changes in atmospheric conditions around the rotating blade for the upward leader initiation. A 2D computational fluid dynamics model was established to obtain the air pressure distribution around the blades, and the simplified inception model was used to determine the initiation of the upward leader mechanism. In this paper, two significant factors of velocity and attack angle were studied. The results show that the trigger height is about an 11.2% difference for 120 m/s with the peak current of return stroke at 30 kA; the difference has reached about 28% for the attack angle of 10°. The research indicates that the area with higher air pressure is exposed to a greater risk of lightning strikes, and the probability of lightning strikes will increase as the blade attack angle increases.